Syd Hoff's Danny and the dinosaur and the girl next door - Hale, Bruce; Hoff, Syd, 1912-2004 (I can read book., 2017)
When Betty, a new neighbor, moves in next door, Danny wants her to meet the dinosaur he enjoys visiting at the museum.